Reformulation of Business Strategies for Increasing Sales of TIN Product Stabilizer at PT Timah Industri - Sundoyo, Hadi; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2013)
PT. Timah Industri (PT TI) is a subsidiary of PT. Timah (Persero) Tbk which exploit comparative advantage of its parent company as the second largest tin producer in the world. With these advantages PT TI entered the downstream PVC stabilizer tin base. Starting from the difficulty of selling their products and then raised the question in inventory management. PT TI should immediately take strategic steps to save the tin chemical business continues to lose money from time to time. From the results of an exploratory study on the issue of business acquired four main issues, namely: on the product and marketing, material, financial and managerial. Then advised there are three (3) basic strategies that can be selected as the main basic approaches for achieving the strategic objectives of PT TI market development, product development strategy and strategic alliance strategies. This new formulation of business strategies to use PT TI Business Model Canvas in 2013 and used as the basis for the application of Diamond Strategy until the end of 2015 which includes a focus on the core business, forming strategic alliances, developing a network of distribution channels and financial restructuring in the hope that the business of PT TI can continue to survive and thrive, and sustained in the future.Â Keywords: Business Strategy, Business Model Canvas, Market Penetration, PVC Stabilizer